Frammento, discontinuità, ripetizione (PHILM. Rivista di filosofia e cinema, 2024)
The text aims to examine the aesthetic aspects of the fragment in two cinematic works. In Joseph Losey’s Accident (1967), the stylistic choice organizes the visual and narrative composition of the film, establishing itself as a means of accessing psychic memory that is structured by fragments and associations of images. In Shame (2011), directed by Steve McQueen, accumulation and fragmentation of images thicken in the repetition of the same, at the service of a limitless enjoyment. The analysis of significant sequences from both films seeks to capture the enduring connection between repetition and variation, aiming to delve into the texture of the images.